A Strategic Approach to Plant Optimization. Issue 4 (1st April 2017) - Colson, Chris; Neale, James
ABSTRACT: In an increasingly capital constrained world, the ability to fund business improvement step change programs is becoming increasingly difficult, yet significant opportunities are available across the three primary pillars of maintenance and reliability, energy efficiency and process efficiency. The recent volatility in energy costs and the potential for greenhouse gas emission trading has raised the awareness of industrial energy efficiency in most manufacturing and processing industries, yet there is a real and significant gap between the efficiency opportunities that are available and the level of savings that actually get implemented. In a similar manner, there is ample evidence that the same can be said of most maintenance and reliability programs as well. Process efficiency opportunities are often directly coupled or intrinsically linked to both maintenance and reliability, and energy efficiency step change processes, giving rise to a multidimensional opportunity matrix. It is becoming increasing critical that each of these three pillars is addressed collectively rather than as isolated silos of business improvement opportunities. The rationale for pursuing a multidimensional and integrated approach is twofold; firstly, to maximize the overall economic return across all three opportunity pillars and secondly to prevent counterproductive initiatives that deliver positive results in one pillar, but negative impacts across other aspects of business performance parameters. The rate of return from any proposed maintenance and reliability improvement program can be significantly increased when incorporating associated energy efficiency savings and potential process efficiency drivers impacting on product quality and yield key performance indicators (KPIs). While "spill over" benefits can be a useful means of achieving successful implementation in a capital-constrained business environment, it is equally important to ensure unintended outcomes cause a net loss across the relevant KPI parameters. To successfully achieve step change improvements in reliability, energy efficiency and process efficiency across a business, a higher level strategic approach must be employed. This article will use several case studies to highlight how this can be achieved, focusing on a large milk powder processing plant in New Zealand. Four years ago, two separate projects were initiated, one looking at plant efficiency in detail and the other a maintenance improvement program. To date an overall energy reduction of over 25% has been achieved, with the majority of these savings linked directly to improvements in plant reliability and improved product yield. Energy saving initiatives were also found to have significant impact on plant reliability, with obvious associated spill-over benefits beyond a basic energy cost saving.